Essential Oil Profiling and Antibacterial Activity of Curcuma xanthorrhiza Roxb. Originated from Yogyakarta by GC-MS - Rahman, Catur Aryanto; Rahmawati, Laily Mega; Santosa, Djoko; Indrasetiawan, Puguh; Purwanto, Purwanto (Majalah Obat Tradisional, 2024)
As a tropical country, Indonesia has a large diversity of flora and fauna, including numerous medicinal plants. Although herbs are widely used for medicinal purposes, their pharmacological effect often varies. This variability is frequently attributed to differences in the geographical locations where these plants are grown, leading to variations in the content of active metabolites. In this study, the profile of metabolite content in the essential oil of C. xanthorriza rhizomes was cultivated in three different regions in Yogyakarta, Indonesia, namely Mangunan, Ngawen, and Menoreh. Gas Chromatography-Mass Spectrometry (GC-MS) analysis was employed to assess the metabolite content of essential oil. At the same time, antibacterial activity against Escherichia coli and Staphylococcus aureus was evaluated using the microdilution method. Results indicated that the rhizome from Mangunan has the highest xanthorrhizol content with a percentage area of 21.07%. The Biplot on Principal Component Analysis (PCA) showed that the relationship of compound levels of the three essential oils has no similarity with one another. The Minimum Inhibitory Concentration at 50% (MIC-50) values of C. xanthorriza essential oils from Mangunan, Menoreh, and Ngawen regions were lower in inhibiting the growth of E. coli bacteria (1620.78 ppm; 1777.69 ppm; and 1688.39 ppm, respectively) compared to S. aureus bacteria (3080.80 ppm; 3340.14 ppm; and 2869.54 ppm, respectively).